Digitalisasi Pencatatan Keuangan dan Pendampingan Kepatuhan Perpajakan Melalui Implementasi Laporan Keuangan Berbasis Microsoft Excel pada UMKM Retail Berkah 1 - Tia Isnaeni; Johandri Iqbal; Dwi Novrian Yuliansyah (JURNAL AKUNTANSI BARELANG, 2026)
This study aims to describe the digitization of financial records and tax compliance assistance through the implementation of Microsoft Excel-based financial statements in MSMEs Retail Berkah 1. The problems studied are financial recording that is still carried out manually, unstructured, and the low understanding of business actors of tax obligations. This research uses a qualitative approach with a constructivism paradigm and a descriptive case study design. The research stages include problem identification, design and implementation of a Microsoft Excel-based financial recording system, tax assistance, and evaluation of results. Data is collected through observation, semi-structured interviews and documentation, then analyzed by data organization, coding, theme, and interpretation, and validated through member checking and triangulation. The results of the study show that digitization of financial records increases the regularity and accuracy of financial statements, while tax assistance builds an initial understanding of tax readiness and awareness of MSME actors.